Disaster Management In Kelud Community - Vitaria Wahyu Astuti; Rimawati Rimawati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Indonesia is called a disaster laboratory for the whole world this is because all types of disasters have occurred. One of the natural disasters that often occurs in Indonesia is Mount erupting, this is because there are 127 active volcanoes, one of which is Mount Kelud which is in Kediri East Java. The purpose of this research was to find out how disaster management in the Kelud community in facing Mount Kelud erupting. The design of this research was a qualitative phenomenological study. The population was the Kelud community in Kepung and Puncu districts. The number of participants was 15 people. The data collection process was carried out with online Focus Discussion Group guidelines. Data analysis had identified two important themes in disaster management in the Kelud community. Community in Kelud that is able to live in peace with disasters as evidenced by an understanding of disaster management carried out